Är det okej att sjukskriva sig? : En kvalitativ studie om arbetstagares uppfattningar om korttidssjukfrånvaro i relation till anställningsformen - Strålind, Camilla (2014)
The purpose of this work is to study employee’s views on short-term sick leave in relation to their employment form and its working conditions. The definition of working conditions was based on the demand-control-support theories by Karasek and Theorell.The study builds on nine interviews with employees from the pre-school child care sector within Luleå municipality, representing three different employment forms: permanent, substitute and hourly. The results show that the views on short-term sick leave by the permanently and hourly employed were mainly influenced by their self-image, for instance not seeing themselves as someone who stays at home when they are ill. The substitutes on the other hand were, to a greater degree, affected by perceived opinions from co-workers regarding sick leave, but also by a pressure of being at their employer's disposal, to improve their chances of getting rehired. This indicates that the working conditions and the worker's experiences affect their tendency to report sick. Regarding the perceived work demands, the study shows that the permanently employed, and to some extent also the substitutes, experienced high demands while the hourly employed considered the demands to be fair. The hourly employed experienced a greater level of support from their employer and co-workers compared to that perceived by the substitutes and, to some extent, also the permanently employed. The results support the existence of a centre-periphery structure in the employment form and the working conditions, regarding the ability to control working tasks and the access to supplementary education. The centre group, consisting of the permanently employed, experienced a higher level of control over tasks and better access to education, while workers further away from the centre group had a lower influence over assignments and more restricted access to education. None of the interviewed employees described their working situation as being one with low support, low control and high demands, which was ...